An Agroforestry guide for field practitioners - Xu, Jianchu; Mercado A; He, J.; Dawson, I. (World Agroforestry Centre, 2013)
Over the past several decades, DPR Korea has suffered from extensive land degradation leading to the loss of livelihoods causing increased food insecurity. To restore degraded sloping land, the Ministry of Land and Environmental Protection of DPR of Korea (MoLEP), the Swiss Agency for Development and Cooperation (SDC) and the World Agroforestry Centre (ICRAF), have been promoting the multi-purpose use of trees to transform landscapes and livelihoods using a participatory approach. The emergence of agroforestry as a sloping land management practice in DPR Korea highlights the growth of technology innovations together with user group processes. A user-friendly, bottom-up participatory process is facilitated by technicians and forest rangers and explores new opportunities for the development of locally appropriate technology through interactive learning processes. This manual provides both proved concepts and good practices for field practitioners to integrate agroforestry into land restoration in general and sloping land management in particular in the DPR Korea. The examples documented in this book are based on a ten-year Sloping Land Management (SLM) project in DPR Korea. We will continue to enhance the capacity of field technicians, user groups and other governmental agencies to work together developing new knowledge, innovations and practices for agroforestry in sloping land management.